Indigo Carmine Degradation in Water Induced by a Pulsed Positive Corona Discharge in Air: Discharge and Postdischarge Effects - Ferreyra, Matías Germán (2022)
In recent years, one of the fastest growing technological applications in the field of nonthermal plasmas is the degradation of organic contaminants of water. In this work, the degradation of indigo carmine (IC) in water induced by a pulsed positive corona discharge operating in ambient air is reported. Degradation levels in different volumes of IC in solution with distilled water treated with different plasma exposure times immediately after discharge (0 h), and in the postdischarge up to 24 h were examined. To explain the IC discoloration in the postdischarge phase, a chemical model was developed. The stability of the reactive species in solution nitrate (NO3−), nitrite (NO2−) and hydrogen peroxide (H2O2), as well as the properties of the solution (electrical conductivity, pH) were also measured. The results suggest that the hydroxyl radical (OH˙) as well as ozone (O3) are the main oxidizing species during the discharge phase, being primarily formed in the gas phase through plasma-mediated reactions and then transferred to the liquid by diffusion, while the OH˙ production in the bulk liquid through the decomposition of peroxinitrous acid (O=NOOH) plays a major role in the IC degradation during the postdischarge. These results are associated with a noticeably increase in the energy-yield values observed at 24 h post-treatment.